KEPUASAN PELANGGAN BERDASARKAN KUALITAS PRODUK, PELABELAN, KEMASAN, DAN RASA MENGGUNAKAN PELANGGAN SITUBONDO SUPERPOTATOCRUNCH SEBAGAI STUDI KASUS - Arma Putra, Feby; Oktaviani, Tita; Fat'chatus Chanifa Jikhan (KRAKATAU (Indonesian of Multidisciplinary Journals), 2025)
Superpotatocrunch Situbondo customers are the subject of this research. The purpose of this study was to determine how the quality, packaging, labeling, and guarantee of Superpotatocrunchs Situbondo affect customer satisfaction. Purposive sampling was used in this study to collect information from 100 people using surveys, interviews, and observations. The goal is to find out how respondents view each variable. Multiple linear regression analysis, data instrument testing (validity and reliability tests), conventional assumption tests (normality, multicollinearity, and heteroscedasticity tests), and hypothesis testing (t and coefficient of determination) were all used in this study. Regression analysis shows that consumer satisfaction is positively influenced by quality (0.230), packaging (0.285), labeling (0.262), and assurance (0.190). Quality, labeling, packaging, and guarantee are all determined by the t test. Customer satisfaction is significantly affected by quality, according to the t test (0.001). Customer satisfaction is significantly affected by packaging test (0.000). Labeling (0.000) has a great impact on customer satisfaction in addition. Customer satisfaction is significantly affected by this guarantee (0.006).